2017
DOI: 10.3390/s17102338
|View full text |Cite
|
Sign up to set email alerts
|

Automated Epileptic Seizure Detection Based on Wearable ECG and PPG in a Hospital Environment

Abstract: Electrocardiography has added value to automatically detect seizures in temporal lobe epilepsy (TLE) patients. The wired hospital system is not suited for a long-term seizure detection system at home. To address this need, the performance of two wearable devices, based on electrocardiography (ECG) and photoplethysmography (PPG), are compared with hospital ECG using an existing seizure detection algorithm. This algorithm classifies the seizures on the basis of heart rate features, extracted from the heart rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
125
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 149 publications
(126 citation statements)
references
References 23 publications
0
125
0
1
Order By: Relevance
“…Currently, a large portion of false detections and a small percentage of missed seizures is caused due to poor ECG quality, largely due to the wiring. A previous study has shown that better performance can be obtained by using a wearable ECG device rather than the standard wired hospital ECG (27). This would however be the case for all evaluated algorithms in this study, including those from the literature tested in this study on the discussed dataset.…”
Section: Limitations Of the Studymentioning
confidence: 80%
See 1 more Smart Citation
“…Currently, a large portion of false detections and a small percentage of missed seizures is caused due to poor ECG quality, largely due to the wiring. A previous study has shown that better performance can be obtained by using a wearable ECG device rather than the standard wired hospital ECG (27). This would however be the case for all evaluated algorithms in this study, including those from the literature tested in this study on the discussed dataset.…”
Section: Limitations Of the Studymentioning
confidence: 80%
“…Personalizing the algorithm will not help to detect these seizures without ictal heart rate changes. Also false detections or missed seizures caused by too strong ECG noise cannot be avoided by the personalization as they can occur both ictally and inter-ictally (27). Other approaches should be used to further improve the performance, such as improved noise removal techniques.…”
Section: Performance Comparison Of the Pi And Tl Approachmentioning
confidence: 99%
“…Behind‐the‐ear EEG is not the only type of signal suitable for a wearable seizure detection system in an outpatient setting. Electrocardiography (ECG), which can be recorded in an outpatient setting, has added value to automatically detect seizures in temporal lobe epilepsy patients . Previous studies investigated multimodal seizure detection algorithms .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, only generalized onset seizure can be detected. [8] This work compared the performance of wrist-worn PPG device and wearable ECG. The result was stated that the performance was good by using wearable EEG.…”
Section: Literature Review On Iot Based Seizure Detection Work Inmentioning
confidence: 99%